Extraskeletal Effects of Vitamin D A Clinical Guide (Contemporary Endocrinology,, 2018)
While the skeletal effects of vitamin D are well-documented, the role and importance of vitamin D outside of bone health has not been well-established. Vitamin D receptors are located in nearly every tissue of the body, and low levels of vitamin D are associated with a range of various diseases. This book provides an in-depth examination of these extraskeletal effects of vitamin D and the associations between vitamin D deficiency and various disease states. Beginning with a review of the biochemistry and physiology of vitamin D, subsequent chapters investigate its relationship to autoimmune and infectious diseases, various forms of cancer, endocrine issues such as diabetes, obesity and reproductive function, cardiovascular disease and muscle weakness. Concluding chapters discuss the role of vitamin D in neurological disorders, including Alzheimer's Disease, and cognitive function. Focusing on extraskeletal effects only across a range of conditions, Extraskeletal Effects of Vitamin D will be an important resource for clinical endocrinologists and primary care physicians.